2020
DOI: 10.21608/ejvs.2020.32462.1178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Royal Jelly Tris-enriched Extender on Buffalo Semen Cryopreservation

Abstract: Royal Jelly (bee's milk) is produced by the hypo-pharyngeal and mandibular glands of the worker honey bees and this is considered the primary food of the honey bee queen and honey bee larvae during the first three days of its life [5]. Royal jelly is composed of proteins, lipids, sugars, vitamins and essential amino acids [6,7]. Royal jelly has a beneficial biological activity in different cells and tissues of laboratory animals [8]. Royal jelly has antibacterial effect [9]. The objective of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Thus, it is clear that bee byproducts—propolis, royal jelly, and bee pollen—allow for the improvement of sperm characteristics during semen preservation. These findings are in agreement with the studies of [ 15 , 16 ] on propolis, [ 18 , 19 ] on royal jelly, and [ 20 , 21 , 22 ] on pollen grains, confirming the potential of bee byproducts for preserving semen through cooling and freezing. The positive effect of BBE on sperm quality is due to its beneficial unique structural components allowing the preservation of sperm cells as effectively as other bee byproducts.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, it is clear that bee byproducts—propolis, royal jelly, and bee pollen—allow for the improvement of sperm characteristics during semen preservation. These findings are in agreement with the studies of [ 15 , 16 ] on propolis, [ 18 , 19 ] on royal jelly, and [ 20 , 21 , 22 ] on pollen grains, confirming the potential of bee byproducts for preserving semen through cooling and freezing. The positive effect of BBE on sperm quality is due to its beneficial unique structural components allowing the preservation of sperm cells as effectively as other bee byproducts.…”
Section: Discussionsupporting
confidence: 91%
“…Modification of semen extenders by adding natural bee byproducts for preserving sperm may enhance sperm characteristics, provide energy, and control bacterial contamination or antioxidant activity, thus enabling fertilization [ 17 ]. Moreover, several authors have reported that various factors influence the preservability of spermatozoa through cooling or freezing, particularly by affecting the osmotic stress, ice crystal formation, toxicity of the cryoprotectants, and the sensitivity to cryoinjury, which is variable among species [ 1 , 11 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation